2017
DOI: 10.1371/journal.pone.0179330
|View full text |Cite
|
Sign up to set email alerts
|

The association between various smoking behaviors, cotinine biomarkers and skin autofluorescence, a marker for advanced glycation end product accumulation

Abstract: BackgroundSkin autofluorescence, a biomarker for advanced glycation end products (AGEs) accumulation, has been shown to predict diabetes-related cardiovascular complications and is associated with several environmental and lifestyle factors. In the present study, we examined the association between various smoking behaviors and skin autofluorescence, as well as the association between several cotinine biomarkers and skin autofluorescence, using both epidemiological and metabolomics data.MethodsIn a cross-secti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 55 publications
4
20
1
Order By: Relevance
“…As if the production of AGEs is matched by the additional removal of AGEs with convective clearance during haemodialfiltration, then levels would not be expected to increase, whereas depending upon the dialyzer membrane pore size, then AGE could accumulate in haemodialysis patients, once residual renal function had been lost . Although some previous reports have demonstrated an association between smoking status and SAF, we were unable to demonstrate an association.…”
Section: Discussionmentioning
confidence: 56%
“…As if the production of AGEs is matched by the additional removal of AGEs with convective clearance during haemodialfiltration, then levels would not be expected to increase, whereas depending upon the dialyzer membrane pore size, then AGE could accumulate in haemodialysis patients, once residual renal function had been lost . Although some previous reports have demonstrated an association between smoking status and SAF, we were unable to demonstrate an association.…”
Section: Discussionmentioning
confidence: 56%
“…The present results extend previous findings from studies in the Netherlands and China that had relatively small numbers of subjects. 22 , 23 However, the age-specific mean SAF values were moderately different among those studies ( Table 2 ). Among individuals aged <60 years, the mean SAF values tended to be higher in our study than among those previously reported.…”
Section: Discussionmentioning
confidence: 89%
“…34 In previous studies, SAF levels were shown to be elevated among cigarette smokers, although in a small number of subjects. 22 , 23 , 35 Additionally, a smoking history may have an impact on SAF, with ex-smokers having higher levels than those who have never smoked. 36 , 37 Consistent with these previous findings, we found that a longer smoking history was correlated with increases in SAF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The accumulation of tobacco-sourced AGEs in the skin can be assessed by using the autofluorescence (SAF) technique. Waateringe et al used the AGE Reader to assess skin AGEs derived from active and secondhand cigarette smoke exposure, along with smoking withdrawal, in healthy individuals and diabetic patients (45). High SAF levels were correlated with diabetic active smokers and SAF intensity was correlated with the hours of cigarette smoke exposure.…”
Section: The Correlation Between Nicotine and Advanced Glycation End mentioning
confidence: 99%